2023
DOI: 10.1002/inf2.12401
|View full text |Cite
|
Sign up to set email alerts
|

Advances in thermal‐related analysis techniques for solid‐state lithium batteries

Abstract: Solid‐state lithium batteries (SSLBs) have been broadly accepted as a promising candidate for the next generation lithium‐ion batteries (LIBs) with high energy density, long duration, and high safety. The intrinsic non‐flammable nature and electrochemical/thermal/mechanical stability of solid electrolytes are expected to fundamentally solve the safety problems of conventional LIBs. However, thermal degradation and thermal runaway could also happen in SSLBs. For example, the large interfacial resistance between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 173 publications
0
9
0
Order By: Relevance
“…Based on the mechanism of battery heat generation, 42 the electrode reaction during battery charging mainly exhibits an endothermic reaction. During high‐current charging, the battery voltage quickly reaches the upper limit cutoff voltage due to the polarization inside the liquid LIB, and the thermal behavior at this stage has not reached a steady‐state condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the mechanism of battery heat generation, 42 the electrode reaction during battery charging mainly exhibits an endothermic reaction. During high‐current charging, the battery voltage quickly reaches the upper limit cutoff voltage due to the polarization inside the liquid LIB, and the thermal behavior at this stage has not reached a steady‐state condition.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to accurately establish the liquid LIB thermal model, it is necessary to understand the heat generation mechanism of liquid LIBs. With the increasing maturity of all-solid-state electrolyte batteries (ASSEBs) technology in recent years, [38][39][40] some studies have also shown that they also have the risk of thermal runaway, 41,42 and different materials and process conditions have a great impact on the performance of the battery. Thus, it is necessary to study the thermal model of ASSEBs to provide a reference for the design.…”
mentioning
confidence: 99%
“…To achieve enhanced electrochemical behavior, it is necessary to directly modify the interface conditions, for example, by reducing interface resistances to facilitate charge carrier transport during electrochemical reactions. [62,63] Additionally, since interface properties are in a dynamic state, interface stability is also crucial for stable electrochemical behaviors during long-term charge-discharge cycles. [64,65] In a rechargeable Li-based battery device, which is a typical device studied in interface research, ion migration continuously takes places between the cathode and anode during the charge-discharge operation, along with varying time/potential.…”
Section: Interfaces In 3d Printing Of Energy Storagementioning
confidence: 99%
“…To achieve enhanced electrochemical behavior, it is necessary to directly modify the interface conditions, for example, by reducing interface resistances to facilitate charge carrier transport during electrochemical reactions. [ 62,63 ] Additionally, since interface properties are in a dynamic state, interface stability is also crucial for stable electrochemical behaviors during long‐term charge–discharge cycles. [ 64,65 ]…”
Section: Interfaces In 3d Printing Of Energy Storagementioning
confidence: 99%
“…[ 4,5 ] Consequently, a wide variety of inorganic solid‐state electrolytes (SSEs) with high shear modulus, have experienced prosperity in recent years since they were believed to be able to physically combat dendritic Li growth. [ 6–13 ] Within this group, sodium superionic conductor (NASICON)‐type SSEs have attracted plenty of attention due to their high ionic conductivity (10 −3 –10 −4 S cm −1 at 25 °C), wide electrochemical window (up to 6 V) and superior air stability. [ 14 ] Nevertheless, the interfacial incompatibility between SSE and Li anode, involving the poor physical contacts of SSE | Li interface and the inherent chemical instability of SSE towards Li anode, leads to a high interface resistance and causing a large local current density, consequently triggering inhomogeneous Li deposition and accelerating Li propagation in SSE.…”
Section: Introductionmentioning
confidence: 99%